MAPK-kinase mutations and aortic lesions are associated with distribution of circulating monocytes in histiocytosis - Jerome Razanamahery; Helene Greigert; Matthias Papo; Jean-Francois Emile; Julien Guy; Francesco Pegoraro; Julien Haroche; Sylvain Audia; Maxime Samson; Bernard Bonnotte (Haematologica)
Not available.